Sintesis Bio-nanosurfaktan sebagai Deterjen Ramah Lingkungan dari Kombinasi Ekstrak Getah Pepaya (Carica papaya L) dan Daun Sengon (Paraserianthes falcataria L. Nielsen) - Tunjung Wahyu Widayati; Hendri Yudisai; I K Gary Devara (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2018)
The purpose of this research is to study formulations Bio-Nano Surfactant by combining papaya sap, Sengon leaf, and HCl to obtain the most efficient concentration in neutralizing calcium oxalate, determine the effect of detergency by Bio-Nano Surfactant and determine the level of contamination by Bio-Nano Surfactant". Detergent formulations using completely randomized design (CRD) with two factors of HCl (0.1%, 0.15%, 0.2%, 0.4%, 0.6%) and papaya sap- sengon leafs concentration (10%, 20%, 30%). The indicator of this research is based on the best combination of parameters to decrease calcium oxalate, protease enzyme levels, and the highest detergency effectiveness in cleaning the substrat. After detergency test, combination of 10% papaya sap - Sengon leafs and 0.2% HCL comes as the best combination. For nanofication, the best sample split into two samples with and without PEG 4000 as nanoparticles template. The samples after nanofication has nano size orde which are the sample with PEG 4000 is smaller (458-686nm) than the sample without PEG 4000 (703-897nm). The detergency of nanoficated samples are higher than before. The results of contaminant level "Bio-Nano Surfactant" is 165.2 ppm for COD and 21.6 ppm for BOD which is lower than COD and BOD limits.